THU0392 PATIENT JOURNEY TO DIAGNOSIS OF ANKYLOSING SPONDYLITIS AND ITS TREATMENT PATTERNS ACROSS CENTRAL EASTERN EUROPE AND THE UNITED STATES. (2nd June 2020) - Korotaeva, T.; Dina, O.; Holdsworth, E.; Fallon, L.; Milligan, G.; Meakin, S.; Wang, L.; Vasilescu, R. S.; Cappelleri, J. C.; Deodhar, A.
Abstract : Background: Long delays in the diagnosis of ankylosing spondylitis (AS) and in receiving advanced therapies signify a critical unmet need. Little is known about delays or treatment patterns in Central Eastern European (CEE) countries. Objectives: To describe patient time to diagnosis of and its treatment patterns in CEE and the US. Methods: Data were collected via a cross-sectional survey of rheumatologists in Czech Republic, Poland, Russia, Ukraine (Sept–Dec 2019) and US (Jun–Aug 2018) via physician-completed patient record forms. In consecutive patients with a physician-reported diagnosis of AS, rheumatologists recorded patient demographics, clinical features, time to first consultation and diagnosis and treatment history. Data were compared for CEE vs US using t-test for independent samples (continuous outcomes) and Fisher's exact test (categorical outcomes). Low rates of HLA-B27 and sacroiliitis at diagnosis may reflect combining non-radiographic axial spondyloarthritis under the diagnosis of AS in real-world practice. Results: 209 physicians (121 CEE; 88 US) provided data for 1363 patients (876 CEE; 487 US). While some demographic differences existed between regions, estimated prevalence of HLA-B27 in patients with AS was the same between US and CEE. Not all patients were stated to have sacroiliitis at diagnosis (Table 1 ). Time to first consultation and time to diagnosis were longer in CEE, with more patients experiencing a delay due to another condition initially being diagnosed (Table 2 ). At diagnosis a similar proportion of patients in CEE and US were prescribed NSAIDs, with higher use of csDMARDs in CEE. bDMARDs were more commonly prescribed at diagnosis in the US, with increased usage continuing after diagnosis (Figure 1 ). Conclusion: Time to diagnosis was three times longer in CEE vs the US. Despite similar prescription of NSAIDs at diagnosis in US and CEE, a greater proportion of patients currently received NSAIDs and csDMARDs in CEE, while bDMARD use in the US was greater. This suggests different treatment approaches and differences in medication access across the regions. Disclosure of Interests: Tatiana Korotaeva Grant/research support from: Pfizer, Consultant of: Abbvie, BIOCAD, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck Sharp & Dohme, Novartis, Novartis-Sandoz, Pfizer, UCB, Speakers bureau: Abbvie, BIOCAD, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck Sharp & Dohme, Novartis, Novartis-Sandoz, Pfizer, UCB, Oluwaseyi Dina Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Elizabeth Holdsworth Employee of: Adelphi Real World, Lara Fallon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Gary Milligan Employee of: Adelphi Real World, Sophie Meakin Employee of: Adelphi Real World, Lisy Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Radu Serban VASILESCU Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Joseph C Cappelleri Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Atul Deodhar Grant/research support from: AbbVie, Eli Lilly, GSK, Novartis, Pfizer, UCB, Consultant of: AbbVie, Amgen, Boehringer Ingelheim, Bristol Myer Squibb (BMS), Eli Lilly, GSK, Janssen, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, Amgen, Boehringer Ingelheim, Bristol Myer Squibb (BMS), Eli Lilly, GSK, Janssen, Novartis, Pfizer, UCB